Looking Inside the Black Box of “Attendance at Services”: New Measures for Exploring an Old Dimension in Religion and Health Research - Idler, Ellen L. (2009)
Research in religion and health has spurred new interest in measuring religiousness. Measurement efforts have focused on subjective facets of religiousness such as spirituality and beliefs, and less attention has been paid to congregate aspects, beyond the single item measuring attendance at services. We evaluate some new measures for religious experiences occurring during congregational worship services. Respondents (N=576) were religiously-diverse community-dwelling adults interviewed prior to cardiac surgery. Exploratory factor analysis of the new items with a pool of standard items yielded a readily interpretable solution, involving seven correlated but distinct factors and one index variable, with high levels of internal consistency. We describe religious affiliation and demographic differences in these measures. Attendance at religious services provides multifaceted physical, emotional, social, and spiritual experiences that may promote physical health through multiple pathways.